Bioinformatics Analyses Reveal Age‐Specific Neuroimmune Modulation as a Target for Treatment of High Ethanol Drinking. (11th October 2013) - Agrawal, Rajiv G.; Owen, Julie A.; Levin, Patricia S.; Hewetson, Aveline; Berman, Ari E.; Franklin, Scott R.; Hogue, Ryan J.; Chen, Yukun; Walz, Chris; Colvard, Benjamin D.; Nguyen, Jonathan; Velasquez, Oscar; et al.
<x xml:space="preserve">Abstract</x> Background Use of in silico bioinformatics analyses has led to important leads in the complex nature of alcoholism at the genomic, epigenomic, and proteomic level, but has not previously been successfully translated to the development of effective pharmacotherapies. In this study, a bioinformatics approach led to the discovery of neuroimmune pathways as an age‐specific druggable target. Minocycline, a neuroimmune modulator, reduced high ethanol (EtOH) drinking in adult, but not adolescent, mice as predicted a priori. Methods Age and sex‐divergent effects in alcohol consumption were quantified in FVB/NJ × C57BL/6J F1 mice given access to 20% alcohol using a 4 h/d, 4‐day drinking‐in‐dark (DID) paradigm. In silico bioinformatics pathway overrepresentation analysis for age‐specific effects of alcohol in brain was performed using gene expression data collected in control and DID‐treated, adolescent and adult, male mice. Minocycline (50 mg/kg i.p., once daily) or saline alone was tested for an effect on EtOH intake in the F1 and C57BL/6J (B6) mice across both age and gender groups. Effects of minocycline on the pharmacokinetic properties of alcohol were evaluated by comparing the rates of EtOH elimination between the saline‐ and minocycline‐treated F1 and B6 mice. Results Age and gender differences in DID consumption were identified. Only males showed a clear developmental increase difference in drinking over time. In silico analyses revealed neuroimmune‐related pathways as significantly overrepresented in adult, but not in adolescent, male mice. As predicted, minocycline treatment reduced drinking in adult, but not adolescent, mice. The age effect was present for both genders, and in both the F1 and B6 mice. Minocycline had no effect on the pharmacokinetic elimination of EtOH. Conclusions Our results are a proof of concept that bioinformatics analysis of brain gene expression can lead to the generation of new hypotheses and a positive translational outcome for individualized pharmacotherapeutic treatment of high alcohol consumption.